FACTORS OF SPEECH CULTURE FORMATION IN FUTURE LAWYERS. - Karimova Gulshod Mamatkadirovna (Journal of new century innovations, 2022)
This article considers the culture of speech as an academic discipline. As well as the analysis of the study of speech in higher education as an integral part of the cycle of humanitarian disciplines, designed for students of all disciplines.